The Validity of Biology Interactive E-book based Scientific Literacy to Improve Student’s Creative Thinking Skills to Support SDG 4 - Puji Rahayu; Endang Susantini; Sunu Kuntjoro (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study aims to describe the validity of Biology Interactive E book Based on Scientific Literacy to Improve Students’s Creative Thinking Skills. The developed Biology Interactive E book Based on Scientific Literacy to Improve Students’s Creative Thinking Skills validity is evaluated in terms of content feasibility, presentation feasibility, and language feasibility. Method: This research is a development research with a ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), which is modified in the Postgraduate Program in Science Education at the State University of Surabaya and implemented in SMA N 1 Bancar, Tuban, East Java. The data collection technique was carried out using the ebook validation method. Results: The assessment instrument used was a e book validation sheet used by two biology lecturers as validators. Data analysis was carried out quantitatively. The validation results of this inquiry-based textbook obtained an average score of 92.25% with a very valid category. Novelty: Based on the analysis of the data obtained, it can be concluded that the Biology Interactive E book Based on Scientific Literacy to Improve Students’s Creative Thinking Skills that has developed are valid and suitable for use in learning. The development of interactive e-books is one part of realizing quality education (SDG 4) in the era of technology adoption.